The Ratio of the Vowel Quantities in the South-West Aukštaitian Dialect - Kazlauskienė, Asta (Kalbotyra, 1998)
This article presents an experimental investigation as well as a statistical evaluation of the quantity of long and short, stressed and unstressed vowels in word-medial and word final position in the Kaunas southern region, the west Aukštaitian dialect. The results show that all (both stressed and unstressed) word-final vowels in the dialect investigated are being shortened.The quantity reduction of unstressed word-medial vowels is also characteristic of the south-west Aukštaitian dialect. The long unstressed vowels are the longest in pre-stressed position, while their length in the post-stressed syllable of the stem and unstressed word-final position is alike. The short unstressed vowels are the longest in pre-stressed position and they are shorter in post-stressed position in the stem; in word-final position they are the shortest.So, in the south-west Aukštaitian dialect the long vowels are used in stressed non-final syllables, the half-long ones are used in all unstressed syllables and in stressed endings instead of the long vowels. The short vowels may occur in stressed and unstressed medial and final syllables.